2013
DOI: 10.1098/rspb.2013.0528
|View full text |Cite
|
Sign up to set email alerts
|

Reception and learning of electric fields in bees

Abstract: Honeybees, like other insects, accumulate electric charge in flight, and when their body parts are moved or rubbed together. We report that bees emit constant and modulated electric fields when flying, landing, walking and during the waggle dance. The electric fields emitted by dancing bees consist of low-and high-frequency components. Both components induce passive antennal movements in stationary bees according to Coulomb's law. Bees learn both the constant and the modulated electric field components in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 30 publications
2
87
1
4
Order By: Relevance
“…These results differ from other recent studies that emphasized the role of antennal mechanosensors of honey bees (Apis mellifera) (8) and cockroaches (9) in responding to electric charge. Greggers et al (8) found that, in addition to the list of known sensory stimuli used by honey bees to communicate their movements to hive mates during the waggle-dance (10), they sense the modulations of the amplitude of the electric fields on their bodies as they move their abdomens and wings closer to or away from neighboring bees.…”
contrasting
confidence: 56%
“…These results differ from other recent studies that emphasized the role of antennal mechanosensors of honey bees (Apis mellifera) (8) and cockroaches (9) in responding to electric charge. Greggers et al (8) found that, in addition to the list of known sensory stimuli used by honey bees to communicate their movements to hive mates during the waggle-dance (10), they sense the modulations of the amplitude of the electric fields on their bodies as they move their abdomens and wings closer to or away from neighboring bees.…”
contrasting
confidence: 56%
“…Bees have been found to exploit changes in electric fields as a means of communication (Greggers et al 2013), opening up new avenues for research and sensor development.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the employment of any electrostatic charge to establish the thread's structure can be excluded. Being charged could actually counteract the purpose of the capture threads as insects can sense electric fields (Clarke et al, 2013;Greggers et al, 2013;Sutton et al, 2016). Hence, a charged capture thread would be detected and avoided by potential prey.…”
Section: Discussionmentioning
confidence: 99%